2020
DOI: 10.1021/acs.jafc.0c04274
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Sensory Characteristics of Soy Sauce: A Review

Abstract: Soy sauce is a fermented product, and its flavor is a complex mixture of individual senses which, in combination, create a strong palatable condiment for many Eastern and Western dishes. This Review focuses on our existing knowledge of the chemical compounds present in soy sauce and their potential relevance to the flavor profile. Taste is dominated by umami and salty sensations. Free amino acids, nucleotides, and small peptides are among the most important taste-active compounds. Aroma is characterized by car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
104
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(106 citation statements)
references
References 88 publications
1
104
0
1
Order By: Relevance
“…It has been generally suggested that ganjang fermentation is processed through ganjang microbiota ( 1 , 2 , 6 , 27 ). Our analysis also showed that Tetragenococcus -mediated heterotactic acid fermentation using free sugars and glycerol was the major fermentation process during ganjang fermentation ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It has been generally suggested that ganjang fermentation is processed through ganjang microbiota ( 1 , 2 , 6 , 27 ). Our analysis also showed that Tetragenococcus -mediated heterotactic acid fermentation using free sugars and glycerol was the major fermentation process during ganjang fermentation ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Some furan derivatives reportedly have characteristic odor descriptions. For example, furan compounds such as 2-pentylfuran, 2,3-dihydro-benzofuran, and 2-N-octylfuran are characterized by strongly scented, sweet, and (in some cases) burnt odor notes, and are generally considered to be important aromatic compounds that contribute greatly to the flavors of soy sauce (Diez-Simon et al, 2020 ). Lactones are produced by unsaturated fatty acids such as linoleic acid and oleic acid during fermentation.…”
Section: Fermentation Dynamic Metabolic Changes Derived From Microorganismsmentioning
confidence: 99%
“…The aroma compounds of many foods are complex, and it is recognized that the aroma is not simply equal to the sum of its aroma compounds [ 9 , 10 ]. Perceptual interactions are indeed found for the aroma compounds.…”
Section: Introductionmentioning
confidence: 99%